2018
DOI: 10.2188/jea.je20170041
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence of the Association Between Handgrip Strength, Hand Dexterity, and Cognitive Performance in Community-Dwelling Older Adults: A Systematic Review

Abstract: BackgroundDeterioration of hand motor function is a possible risk factor of cognitive impairment in older adults. Despite a growing body of research, a lack of clarity exists regarding the relationships. This review offers a synthesis of existing observational studies evaluating the associations of handgrip strength and hand dexterity with cognitive performance in community-dwelling older adults.MethodsPubMed, PsycINFO, and ScienceDirect were systematically searched (search dates: 1990–2016), and relevant arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 59 publications
6
47
0
1
Order By: Relevance
“…A number of epidemiologic prospective studies have demonstrated an inverse association between late-life handgrip strength and cognitive function in elderly populations. [34][35][36][37] A scoping review revealed a clear relationship between lower handgrip strength and the progression of cognitive decline. 17 Likewise, lower late-life handgrip strength has been reported to be significantly associated with a greater risk of total dementia in several prospective studies of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiologic prospective studies have demonstrated an inverse association between late-life handgrip strength and cognitive function in elderly populations. [34][35][36][37] A scoping review revealed a clear relationship between lower handgrip strength and the progression of cognitive decline. 17 Likewise, lower late-life handgrip strength has been reported to be significantly associated with a greater risk of total dementia in several prospective studies of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review examining the relationship between grip strength and cognitive function in older adults, Kobayashi-Cuya et al reported that 6 of 7 studies documented significant relationships. 51 Vancampfort et al recently reported that among middle-aged and older adults, weak grip strength was associated with increased odds of having mild cognitive impairment. 52 Others have shown a correlation between grip strength and the Mini-Mental State Examination scores of geriatric inpatients, 53 information processing speed and executive functioning of patients attending a memory clinic, 54 Stroop Task and 6item Cognitive Impairment Test scores of physically active adults, 55 visual memory,and reaction time of patients with schizophrenia, 56 and Animal Fluency Test and Digital Symbol Substitution Test scores of cancer survivors.…”
Section: Grip Strength As a Biomarker Of Current Statusmentioning
confidence: 99%
“…In the first review, Kobayashi-Cuya et al concluded that while grip strength and cognition are associated longitudinally, it is not clear "which variable at baseline affects the other in the long-term." 51 In the second review, Zammit et al opined that while both grip strength and cognitive performance decline with age, evidence for an association between longitudinal rates of change in the variables is limited. 118 Several original studies not included in the aforementioned reviews provide evidence supporting a predictive relationship between grip strength and cognitive decline.…”
Section: Grip Strength As a Biomarker Of Future Outcomesmentioning
confidence: 99%
“…The gait speed and handgrip strength represented the core determinants of physical frailty and sarcopenia, which were reported to be associated with cognitive impairment and decline [12,14,15]. Previous studies have also shown that physical function parameters, such as gait speed and handgrip strength, are associated with cognitive function in older people [15][16][17]. Therefore, we explored gait speed and handgrip strength as physical function indicators in this study.…”
Section: Introductionmentioning
confidence: 99%